Pengaruh Pembiayaan Kredit KUR Terhadap tingkat Pendapatan UMKM pada Bank BRI Syariah Kota Bengkulu - Erwin Febriansyah; Melda Yunita; Hardiansyah Hardianysah (Universitas Muhammadiyah Bengkulu, 2021)
This study aimed at finding out the effect of Peopleâ€™s Business Credit (PBC) for credit financing on Small Micro Medium Enterprises (SMMEs) income levels. This study employed the Qualitative method.Â The type of study used primary data obtained directly in the field by distributing questionnaires to SMMEs that make PBC loans to BRI Syariah Bank Bengkulu city. The populations of this study were SMMEs which borrowed capital from BRI Syariah Bank Bengkulu city with a sample of 67 SMMEs selected by Random Sampling method, while for data analysis, the study applied simple linear regression analysis using test equipment, Simultaneous Test (F Test), Partial Test (Test T), Test the coefficient of determination (adjusted R2). The results of the study demonstrate that: PBC Credit Financing has contributed an effect on Income Levels of 0.00 <0.05. Therefore, it can be concluded that PBC credit financing has a positive effect on income levels. It is looked forward to further research is able to take more samples number so that the research carried out significantly reflects the trully state of the business people.Keywords : Financing or Credit, Income Level, SMMEs